A Systematic Literature Review on Smart City Project Initiatives for Rural Community Participation - Bin Man, Mohamad Nur Salam; Abdul Manaf, Halimah (Journal of Social Transformation and Regional Development, 2022)
Most democratic governments have prioritised offering people more significant input in government decision-making and promoting public participation in policy creation. People and governments may now effectively integrate formerly unsurmountable gaps in their relationships thanks to advances in digital and information technologies. "Smart City" technologies are not a new term in today's urbanisation development field; however, this "Smart City" technologies term is likely unfamiliar with the rural area, as the rural area is sometimes assumed to perform poorly in the development of innovative city initiatives, which are mostly being pioneered by the local government authority with a focus on a city or urban region. Citizens can now participate in decision-making and policy-making due to the smart city project initiative, which cannot be disregarded entirely; unfortunately, rural population participation remains limited. This conceptual research aims to examine smart city project aspirations for the rural community public participation framework. The author comprehends the importance of including significant public participation in all parts of the planning process. The methodology behind this research is based on a detailed study of the scholarly literature that has already been done. The conclusions of the research were derived from a number of different reading materials, such as books, journals, and other sources on smart city programmes for public participation in rural areas.